2010
DOI: 10.1155/2010/583691
|View full text |Cite
|
Sign up to set email alerts
|

Organogenic Nodule Formation in Hop: A Tool to Study Morphogenesis in Plants with Biotechnological and Medicinal Applications

Abstract: The usage of Humulus lupulus for brewing increased the demand for high-quality plant material. Simultaneously, hop has been used in traditional medicine and recently recognized with anticancer and anti-infective properties. Tissue culture techniques have been reported for a wide range of species, and open the prospect for propagation of disease-free, genetically uniform and massive amounts of plants in vitro. Moreover, the development of large-scale culture methods using bioreactors enables the industrial prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 124 publications
0
6
0
Order By: Relevance
“…PAs are growth regulators that have been implicated in abiotic and biotic stresses (Cona et al, 2006; Cuevas et al, 2008; Marina et al, 2008; Alcázar et al, 2010; Gonzalez et al, 2011; Nambeesan et al, 2012; Agudelo-Romero et al, 2014; Minocha et al, 2014; Pál et al, 2015), as well as in plant morphogenesis and development (Applewhite et al, 2000; Fortes et al, 2010, 2011; Tiburcio et al, 2014; Jancewicz et al, 2016), senescence (Pandey et al, 2000; Sobieszczuk-Nowicka, 2017), and fruit development and ripening (Mattoo and Handa, 2008; Agudelo-Romero et al, 2013, 2014; Tavladoraki et al, 2016). Several publications have suggested that the role played by these growth regulators in plant–microbe interactions is either exerted directly by PAs functioning as signaling molecules or mediated through the products of their catabolism together with jasmonic acid (JA), abscisic acid (ABA), salicylic acid (SA), auxins, cytokinins, and ethylene (Jiménez-Bremont et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…PAs are growth regulators that have been implicated in abiotic and biotic stresses (Cona et al, 2006; Cuevas et al, 2008; Marina et al, 2008; Alcázar et al, 2010; Gonzalez et al, 2011; Nambeesan et al, 2012; Agudelo-Romero et al, 2014; Minocha et al, 2014; Pál et al, 2015), as well as in plant morphogenesis and development (Applewhite et al, 2000; Fortes et al, 2010, 2011; Tiburcio et al, 2014; Jancewicz et al, 2016), senescence (Pandey et al, 2000; Sobieszczuk-Nowicka, 2017), and fruit development and ripening (Mattoo and Handa, 2008; Agudelo-Romero et al, 2013, 2014; Tavladoraki et al, 2016). Several publications have suggested that the role played by these growth regulators in plant–microbe interactions is either exerted directly by PAs functioning as signaling molecules or mediated through the products of their catabolism together with jasmonic acid (JA), abscisic acid (ABA), salicylic acid (SA), auxins, cytokinins, and ethylene (Jiménez-Bremont et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…31 It may be that the huge amount of PAs detected in hop nodules 28 days after culture initiation are also related to differential auxin fluxes inside nodules which may lead to organization of nodular vascular centers to which future regenerated plantlets will be connected to. 19,20 It is noteworthy in this context that hop nodules contain higher levels of IAA than internodes. 32 In Scots pine, at the early developmental stages of zygotic embryogenesis there is typically an increasing trend in PA concentrations and a decreasing trend during late embryo development.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 97%
“…Hop, besides being an important ingredient in beer, has very promising health-promoting and medicinal properties given mainly by specific polyphenols. 18,19 In spite of its economical importance, hop is extremely sensitive to several pathogens. Therefore, it is important to continue research towards understanding factors involved on in vitro plant regeneration.…”
Section: Adc Accumulation Throughout Organogenic Nodule Formationmentioning
confidence: 99%
“…Humulus lupulus L., commonly known as hop, is a dioecious perennial, climbing plant, belonging to the Cannabaceae family native to Northern temperate climates [1]. Hop plants have a long and proven history of their use in herbal medicine, mainly due to their sedative, tonic and calming effect [2], but its importance in beer production as a main ingredient remains of great value [3]. Female hop inflorescences (hops, cones or strobiles) have been used in traditional medicine to treat neurological and gynecological disorders [4,5].…”
Section: Introductionmentioning
confidence: 99%